Teknologi Tepat Guna Produksi Sabun Batang Dari Minyak Jelantah di Padang Pariaman - Riani, Pevi; Putri, Melysa; Futeri, Renny; Armin, M. Ikhlas; Samah, Selfa Dewati; Syafrinal, Syafrinal; Hafnimardiyanti, Hafnimardiyanti (Journal of Industrial Community Empowerment, 2022)
Ramuak cracker is one of the main product of Toboh Mandailing, Balai Baru, VII Koto Sungai Sariak, Padang Pariaman, West Sumatera. One of the obstacles faced by the cracker industry players is the amount of used cooking oil produced. Used cooking oil is leftover frying oil that has been repeatedly used. If it continues to be consumed, it will be harmful to health. If discharged into the environment, it will cause environmental pollution. Therefore, the Community Partnership Program Team of the Politeknik ATI Padang provided counseling about the dangers of used cooking oil and efforts to process used cooking oil into something useful, namely producing bar soap with used cooking oil as its raw material. The step of making bar soap from used cooking oil is to slowly dissolve the NaOH solution into 500 grams of used cooking oil, then stir using a stainless steel stirrer until evenly distributed and there are no more lumps. The next step is to add dyes and fragrances and stir again to form a soap mixture. Do the printing of the soap dough in the mold by coating it with parchment paper. Let stand for 24-48 hours until the saponification process is complete. PKM activities carried out well and smoothly and in accordance with the expected results. Each participant was able to make bar soap from used cooking oil very well. This activity is expected to provide insight, knowledge and input to partners regarding the process of making bar soap from used cooking oil so that it can be used for daily needs and can even be sold as an additional source of income for the community.